Bionika Dornaha - Inna Druzhinina (Проект Байкал, 2004)
Wood, this building material, was firstly used as sculptural plastic. The author decided to use it, on the one hand, because of the difficulties in fixing the round surfaces of outside walls, and on the other hand, it was a real «handwork», which turned the building into the exclusive object. Obviously, the simple decor of the first floor and the great decor of the second floor have a philosophical basis and give a unique silhouette to the building.